Pengentasan Buta Aksara Melalui Baca, Tulis, Hitung, Diskusi, dan Aksi (Calistungdasi) di Desa Kawo Kabupaten Lombok Tengah - Andy Agam Maulana (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2024)
Illiteracy is the inability to read, write and count simple sentences. The illiteracy rate for those aged 15-59 years in West Nusa Tenggara Province is still quite high, even above the national figure with a percentage of 7.91%, especially in Central Lombok Regency. Data from the Central Lombok Regency Government shows that up to 2015, 1,970 residents of various ages were recorded as illiterate. The main goal of literacy education is to teach students to be able to utilize the basic skills of reading, writing, arithmetic, discussion and action (Calistungdasi), as well as their functional abilities in everyday life. The objectives of this activity include: 1) so that people are able to read, write and count; 2) so that society is able to compete in facing advances in technology and in social life; 3) so that people can easily accept empowerment programs from the government; and 4) so ​​that people are able to become instructors for other communities. Based on the results of activities, observations and implementation of work programs that have been planned, prepared and implemented, several conclusions can be drawn, including: 1) the success of activities cannot be separated from cooperation between the implementation of activities and village officials, the community and all parties who assist and support the implementation of community service activities. Without good cooperation, the work program will not run smoothly; 2) with the implementation of activities, the community tries to imitate the way of thinking in implementing critical activities, especially for illiterate residents; 3) by carrying out activities, the community is helped by increasing the information and knowledge they obtain from carrying out activities; and 4) implementing activities to gain knowledge and learn how to live from village people, such as: mutual cooperation, friendship, and helping each other.